2011
DOI: 10.1681/asn.2010070777
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Specific Antibodies Accelerate Arteriosclerosis after Kidney Transplantation

Abstract: In biopsies of renal allografts, arteriosclerosis is often more severe than expected based on the age of the donor, even without a history of rejection vasculitis. To determine whether preformed donor-specific antibodies (DSAs) may contribute to the severity of arteriosclerosis, we examined protocol biopsies from patients with (n ϭ 40) or without (n ϭ 59) DSA after excluding those with any evidence of vasculitis. Among DSA-positive patients, arteriosclerosis significantly progressed between month 3 and month 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 24 publications
(33 reference statements)
2
62
0
Order By: Relevance
“…In heart, the role of anti-HLA antibodies in acceleration of cardiac allograft vasculopathy has emerged (19,20), pointing towards the importance of antibody-mediated injury as a major culprit in many longterm failing organs including hearts, but also other solid organ transplants such as lungs, small bowel, composite tissue transplants, and kidney allografts (15,(21)(22)(23). The latter has recently been supported by the demonstration of a new rejection entity called antibody-mediated vascular rejection, characterized by circulating allo anti-HLA antibodies inducing intimal arteritis and microcirculation inflammation followed by accelerating allograft arteriosclerosis and long-term allograft failure (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…In heart, the role of anti-HLA antibodies in acceleration of cardiac allograft vasculopathy has emerged (19,20), pointing towards the importance of antibody-mediated injury as a major culprit in many longterm failing organs including hearts, but also other solid organ transplants such as lungs, small bowel, composite tissue transplants, and kidney allografts (15,(21)(22)(23). The latter has recently been supported by the demonstration of a new rejection entity called antibody-mediated vascular rejection, characterized by circulating allo anti-HLA antibodies inducing intimal arteritis and microcirculation inflammation followed by accelerating allograft arteriosclerosis and long-term allograft failure (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this distinct group of antibody-mediated vascular rejection is not yet represented in the current Banff classification. Furthermore, the same group from Paris recently reported that donor-specific antibodies (DSAs) very likely contribute to the severity and progression of arteriosclerosis in renal transplants [41]. Comparing protocol biopsies from patients with and without DSA showed that arteriosclerosis significantly progressed between month 3 and month 12 after transplant in DSA-positive patients while among DSA-negative patients no statistically significant progression was observed during the same timeframe.…”
Section: Cell-mediated Rejectionmentioning
confidence: 99%
“…However, the only accepted diagnostic feature for chronic CMR under Banff criteria is the presence of intimal inflammation in the setting of chronic allograft arteriopathy consisting of arterial intimal fibrosis with mononuclear infiltration and formation of a neo-intima [20]. However, as discussed above, recent data suggest that DSA play a major role in accelerated arteriosclerosis in renal allografts [41]. With progressing IFTA, the renal tubules shrink, acquire wrinkled, thickened tubular basement membranes, and are infiltrated by inflammatory cells.…”
Section: Chronic Cell-mediated Rejectionmentioning
confidence: 99%
“…5,6,12,14,24,25 This could be achieved with biopsies at the time of transplant; at 90 days, 1 year, and later after transplant; 14 and as indicated clinically. In addition to measuring drug blood levels, crossmatch and donor-specific antibodies may be determined monthly or bimonthly during this period, because the levels of donor-specific antibodies (HLA and MICA) after transplant may follow a dynamic and multidirectional mode similar to that observed before transplant.…”
Section: Monitoring Sensitized Patients After Transplantmentioning
confidence: 99%
“…4-7, 9, 11-13 The presence of these antibodies (anti-HLA and anti-non-HLA), even in the absence of a positive historical crossmatch, is associated with an increased risk for allosensitization, accelerated renal arteriosclerosis, and antibody-mediated graft failure. 12,14,15 This risk is amplified with the coexistence of donor-specific antibodies and positive historical crossmatch. 11 In the past, a positive current crossmatch represented an absolute contraindication for transplant.…”
Section: Introductionmentioning
confidence: 99%